Analisis Kelayakan Pengembangan Usaha Peyek Ma’pun Desa Sangubanyu - Suhartini, Titik (Jurnal Ekonomi dan Teknik Informatika (JNETI), 2024)
The Ma'Pun bean project business is a business that processes peanut raw materials into new products that have a higher value, can provide added value because costs are incurred so that new prices are formed which are higher and profits are greater than without going through the processing process. This study aims to find out whether the Ma'Pun project business is feasible to develop. This research used a case study method on the Ma'Pun peanut project in Sangubanyu Village, Grabag District, Purworejo Regency. Furthermore, this research was analyzed descriptively qualitatively and quantitatively. The data collection techniques of this research include observation, documentation, and interviews. The research results show that: (1). The peanut project business profile was established in 2021 until now, the peanut project business scale is the micro- medium scale, the source of capital comes from own capital. (2) Analysis of the non-financial feasibility of the peanut shell business, namely marketing aspects, technical aspects, environmental aspects and legal aspects, is feasible to run because it already has a complete licensing PIRT No 2053306010400-28, (3) Analysis of financial feasibility NPV of IDR 163,361, 98 NPV> 0, the IRR is 380% with an interest rate of 10%, the Net B/C value is 1.50> 1, and the payback period for investment is 3 months 9 days.